Temporal Variation of Rainfall in the Bagmati River Basin, Nepal - Shrestha, Rajendra Man; Sthapit, Azaya Bikram (Nepal Journal of Science and Technology, 2016)
The main aim of the study was to identify the temporal variation of rainfall in the Bagmati River basin, Nepal using data available at Department of Hydrology and Meteorology, Government of Nepal. The time series data for the period of 1981-2008 were analyzed by using non-parametric Mann-Kendal test, Spearman’s’ Rho and a parametric linear regression. The results showed that there was a significantly increasing upward trend of the annual mean of weighted areal rainfall, with a rate of 2.2 mm per year. Trend analysis of the monthly time series of weighted areal rainfall showed a significant upward trend in the months of summer monsoon season (June and July). However, there were no such significant result in the other season/months. The increasing trend in the summer monsoon might lead to severe flooding in future. Nepal Journal of Science and Technology Vol. 16, No.1 (2015) pp. 31-40